HISTOMORPHOLOGICAL ENHANCEMENT OF THE VAGINAL WALL IN DEHYDROEPIANDROSTERONE-TREATED POST-OVARIECTOMIZED WISTAR RATS - Peni, Lis Widodo; Falah, Pilar Menara; Nurdian, Yudha (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Vaginal atrophy has occurred in three quarters of post-menopausal women. The exclusive source of post-menopausal sex hormones is dehydroepiandrosterone (DHEA). Purpose: Observe the impact of orally administered DHEA in the vagina of a rat (Rattus norvegicus) post- bilateral ovariectomy. Method: This experiment utilized 36 wistar rats aged 10 - 12 weeks with a body weight of 180 - 200 grams. The rats were randomly divided into two groups with an equal number of members. The control group was orally administered glycerin via gavage at a dose of 1 mL per day, while the treatment group received 7.2 mg of DHEA dissolved in glycerin, also administered orally via gavage at a daily dose of up to 1 mL. Both groups were maintained for 42 consecutive days. Finally, a histomorphology examination was conducted on the vaginal tissues of the sacrificed rats. Result: The mean of epithelial and smooth muscle thickness of the treatment group was significantly higher than that of the control group (p-value < 0.05). Besides, the number of blood vessels were also significantly higher in the treated group (p-value < 0.05). Conclusion: Administering DHEA orally via gavage enhances epithelial and smooth muscle tissue thickness, and augments the number of blood vessels in the vagina of wistar rats after bilateral ovariectomy.